(2x+9)+(6x+3)=180

Simple and best practice solution for (2x+9)+(6x+3)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+9)+(6x+3)=180 equation:


Simplifying
(2x + 9) + (6x + 3) = 180

Reorder the terms:
(9 + 2x) + (6x + 3) = 180

Remove parenthesis around (9 + 2x)
9 + 2x + (6x + 3) = 180

Reorder the terms:
9 + 2x + (3 + 6x) = 180

Remove parenthesis around (3 + 6x)
9 + 2x + 3 + 6x = 180

Reorder the terms:
9 + 3 + 2x + 6x = 180

Combine like terms: 9 + 3 = 12
12 + 2x + 6x = 180

Combine like terms: 2x + 6x = 8x
12 + 8x = 180

Solving
12 + 8x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 8x = 180 + -12

Combine like terms: 12 + -12 = 0
0 + 8x = 180 + -12
8x = 180 + -12

Combine like terms: 180 + -12 = 168
8x = 168

Divide each side by '8'.
x = 21

Simplifying
x = 21

See similar equations:

| 3/15x-8/15x=3 | | (25b-6)-6(4b+1)=-7 | | -15(X-3)=-25 | | 2X+2(6Y)=126 | | 0.4t=0.7+0.6t | | 5(4x-8)=-20 | | -2(3x+5)+4-7x=6x-18 | | (3P-4)=-25 | | 2.5x=100-2.5x | | 34five+23five= | | 15+9u-3=16+-2u-7 | | 4a^2-11a=3 | | -2/3w-8/15=-4/5 | | 15+9u-3=16-2u-7 | | tan^2x=0.25 | | 3y-27=-15 | | 13/48+x/2-(2x+1)/6=1 | | h=-16t^2+44t+7 | | 6+-2=y | | (x+14)(x+3)=0 | | -4k+2(5k-6)=-3k-30 | | -4(2x+4)=12x-8 | | 4x=6x-3 | | 3x+2x=85 | | 20-18=200 | | .003x-.2=.01 | | 15p+9-11-p=-2(2p+4)-3(2p-2) | | -4(7-2t)=4(t-1) | | 3y*2+3(4y*2-2)= | | y^2+10y=11 | | -5x-6(2x-2)=-107 | | -8(3x+12)-13=4x+10 |

Equations solver categories